2020
DOI: 10.1242/jcs.245571
|View full text |Cite
|
Sign up to set email alerts
|

Sec71 separates Golgi stacks in Drosophila S2 cells

Abstract: Golgi stacks are the basic structural units of the Golgi apparatus. Golgi stacks are separated from each other and scattered in the cytoplasm of Drosophila cells. Here, we report that the ARF-GEF inhibitor Brefeldin A (BFA) induces the formation of BFA bodies, which are aggregates of Golgi stacks, trans-Golgi networks, and recycling endosomes. Recycling endosomes are located in the centers of BFA bodies, while Golgi stacks surround them on their trans sides. Live imaging of S2 cells revealed that Golgi stacks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Recently, Fujii et al (2020b) showed in Drosophila cells that knockdown of Arf GEF Garz also induces dynamic relocalization of Golgi proteins to the ER, while leaving behind GM130, a component of cis -Golgi, in the cytoplasm, again suggesting the existence of a GECCO-like compartment in invertebrate cells (see Figure 4C ). It should be mentioned here that mammalian GM130 was also shown to stay in BFA-resistant structures together with ERGIC ( Nakamura et al, 1995 ).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Recently, Fujii et al (2020b) showed in Drosophila cells that knockdown of Arf GEF Garz also induces dynamic relocalization of Golgi proteins to the ER, while leaving behind GM130, a component of cis -Golgi, in the cytoplasm, again suggesting the existence of a GECCO-like compartment in invertebrate cells (see Figure 4C ). It should be mentioned here that mammalian GM130 was also shown to stay in BFA-resistant structures together with ERGIC ( Nakamura et al, 1995 ).…”
Section: Introductionmentioning
confidence: 82%
“…BFA treatment of Drosophila cells also gave very interesting results ( Fujii et al, 2020b ) ( Figures 4B,C ). Drosophila has two Arf GEFs, called Sec71 (homolog of mammalian BIG and yeast Sec7, which functions in TGN) and Garz (homolog of mammalian GBF1 and yeast Gea1, which functions in cis -Golgi).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations